DISTINCTIVE FEATURES OF HALIMA XUDOYBERDIYEVA’S CREATIVE WORK (International journal of artificial intelligence, 2026)
This article analyzes the distinctive features of the creative work of the poetess Halima Xudoyberdiyeva. The study examines the artistic expression of national identity, female psychology, patriotism, human emotions, and social responsibility in her lyrical poetry. The ideological and artistic orientation of the poetess’s works, her poetic thinking, system of images, and stylistic originality are explored from a scientific and theoretical perspective. In addition, the article substantiates the place and significance of Halima Xudoyberdiyeva’s creative heritage in Uzbek literature.